وحدة التقويم المدرسي (رؤية مقترحة لتفعيل دور التقويم في النهوض بالعملية التعليمية بالمدارس) - جابر, جميلة (University of Eloued جامعة الوادي, 2023)
استهدفت الدراسة الحالية وضع تصور لكيفية تفعيل دور التقويم للنهوض بالعملية التعليمية بالمدارس. واستندت الدراسة إلى المنهج الوصفي. واعتمدت في إطار ذلك على الأسلوب التحليلي. وتمثلت أداة الدراسة في مسح الأدبيات المتعلقة بموضوع الدراسة. وأسفرت الدراسة عن العديد من النتائج أهمها الآتي: وحدة التقويم المدرسي المقترحة عبارة عن فريق عمل بالمدارس يتألف من أهل الخبرة في مجال التقويم ويشاركهم في ذلك عدد من المعلمين، والطلاب، وأفراد من الإدارة المدرسية والآباء – تستهدف هذه الوحدة تناول جميع عناصر المنظومة المدرسية من تلميذ، ومعلم، وإدارة مدرسية، ومناهج ، وطرق تدريس، وتجهيزات بالتقويم التشخيصي والعلاجي – يتسم التقويم الذي تقوم به هذه الوحدة بالشمول، والاستمرار، والتراكمية. وأوصت الدراسة المعنيين بالتعليم المدرسي بالإفادة من التصور الذي اقترحته الدراسة لتفعيل دور التقويم في الارتقاء بالعملية التعليمية بالمدارس . The study aimed at suggesting a proposal to activate the role of academic evaluation so that learning can be improved. The study used the descriptive methodology to reach the targets in question. To gather the required data, a review of literature was administered. The study came to the conclusions that; first, the suggested unit for school evaluation is a school working team that consists of experts in educational evaluation, teachers, students, members of the school administration as well as parents that cooperate in the evaluation's process; second, this unit aims at evaluating all the sub-systems of the school, i., e., students, teachers, principals, psychologists, social workers, curricula, methodologies, aids as well as facilities; third, the evaluation adopted by this unit is characterized with inclusion, continuity and accumulation. The study recommended that steps ought to be taken to put into effect the proposal the study suggests to activate the role of educational evaluation so that learning output can be improved and optimized.
مقال
Keywords: وحدة التقويم المدرسي، العملية التعليمية. ; School Evaluation Unit, Learning